Successful outcome of Epstein–Barr virus encephalitis managed with bilateral craniectomy, corticosteroids and aciclovir. Issue 4 (6th August 2012) - Hayton, Emma; Wakerley, Benjamin; Bowler, Ian CJW; Bogdanovic, Marko; Adcock, Jane Elizabeth
Abstract : We present a 19-year-old woman with severe encephalitis and raised intracranial pressure requiring decompressive craniectomy. Her clinical features were consistent with encephalitis in the context of acute primary Epstein–Barr virus (EBV) infection (infectious mononucleosis). Serology, bone marrow aspirate and PCR of blood and cerebrospinal fluid confirmed the diagnosis. She was treated with corticosteroids and aciclovir. She was critically unwell for 3 weeks, requiring artificial ventilation but eventually made a good recovery. EBV encephalitis is uncommon, making the diagnosis and decisions about clinical management challenging.